The transactional leadership behaviours, learning organization dimensions and job motivation in the schools - Eğriboyun, Dursun (Advances in Social Sciences Research Journal, 2019)
The purpose of this research is to examine the relationship of the school administrator’s transactional leadership behaviours and learning organization dimensions in the educational institutions with the job motivation of the teachers. In order to determine the interrelationship between the concepts, a field study was conducted in 18 schools at the elementary, secondary and high school levels in Izmir in Turkey. The questionnaire form applied to the teachers working in the determined institutions within the cross-sectional research process by a purposive sampling method on the basis of volunteering, and a total of 352 measurement tools is evaluated. The reliability and validity results are examined by applying the confirmatory factor analysis to the scales. According to the obtained findings, a relationship that is significant at enough level and in the same direction is ascertained between the transactional leadership behaviours and the job motivation (r= .383 p<0.01) while a relationship that is significant at medium level and in the same direction is ascertained between the learning organization dimensions and the job motivation (r= 0.696 p<0.01). It can be seen that the model can be accepted according to the obtained values of the goodness of fit, when the model test results are analysed by the structural equation modelling analysis, too.